CORRECTION OF INTERFERON-α-INDUCED DENDRITIC CELL DYSFUNCTIONS IN IMMUNOCOMPROMISED PATIENTS - O. Yu. Leplina; L. V. Sakhno; A. A. Ostanin; S. S. Bogachev; E. R. Chernykh (Acta Biomedica Scientifica, 2012)
The correction of impaired functions of in vitro generated interferon-alpha-induced dendritic cells (IFN-DCs) in patients with malignant brain tumors (n = 8), malignant lymphomas (n = 14) and pulmonary tuberculosis (n = 26) was analyzed in the present study. The principal possibility of restoring reduced functional activity of patient DCs was shown. The addition of recombinant human IL-2, complex of pro-inflammatory cytokines, double-stranded human DNA or polyoxidonium to IFN-DC cultures at the stage of maturation could significantly increase the allostimulatory activity of DCs in patients with malignant lymphomas and pulmonary tuberculosis, as well as enhance the cytotoxic activity of cancer patient DCs against NK- and TRAIL-resistant tumor cell line HEp-2. These findings offer new approaches to the correction of DC dysfunctions in the pathology and justify ways of improving the treatment of infectious diseases and cancer using dendritic cell vaccines.